Differential expression of miRNAs in the presence of B chromosome in the cichlid fish Astatotilapia latifasciata - Nascimento-Oliveira, Jordana Inácio [UNESP] (2021)
Background: B chromosomes (Bs) are extra elements observed in diverse eukaryotes, including animals, plants and fungi. Although Bs were first identified a century ago and have been studied in hundreds of species, their biology is still enigmatic. Recent advances in omics and big data technologies are revolutionizing the B biology field. These advances allow analyses of DNA, RNA, proteins and the construction of interactive networks for understanding the B composition and behavior in the cell. Several genes have been detected on the B chromosomes, although the interaction of B sequences and the normal genome remains poorly understood. Results: We identified 727 miRNA precursors in the A. latifasciata genome, 66% which were novel predicted sequences that had not been identified before. We were able to report the A. latifasciata-specific miRNAs and common miRNAs identified in other fish species. For the samples carrying the B chromosome (B+), we identified 104 differentially expressed (DE) miRNAs that are down or upregulated compared to samples without B chromosome (B−) (p < 0.05). These miRNAs share common targets in the brain, muscle and gonads. These targets were used to construct a protein-protein-miRNA network showing the high interaction between the targets of differentially expressed miRNAs in the B+ chromosome samples. Among the DE-miRNA targets there are protein-coding genes reported for the B chromosome that are present in the protein-protein-miRNA network. Additionally, Gene Ontology (GO) terms related to nuclear matrix organization and response to stimulus are exclusive to DE miRNA targets of B+ samples. Conclusions: This study is the first to report the connection of B chromosomes and miRNAs in a vertebrate species. We observed that the B chromosome impacts the miRNAs expression in several tissues and these miRNAs target several mRNAs involved with important biological processes.